Discourse on Suicide among Students at Yogyakarta Universities - Ajy Waskyto Sugiyanto, Bagus (Kalijaga Journal of Communication, 2024)
Student suicide as a recent phenomenon is always discussed from a psychological and individualist perspective. Therefore, this research has a problem formulation of how regulated statements or discourse regarding DIY student suicide are formed. This research seeks to reveal knowledge about suicide by students. This knowledge is created by discourse. In Archeology of Knowledge (1972: 80), Foucault defines discourse as the "general domain of statement." This research is a type of qualitative research. The data collected is text data reporting suicides of Yogyakarta students. The analysis produces findings that strengthen Marsh's (2010) opinion that suicide cases in this era are seen in mental health discussions. With discussions about mental health, suicide is confused with a psychiatric medical lens that creates awareness of the importance of psychology in society. However, this view creates a reduction in the way suicide is viewed.